Perancangan Sistem Informasi Pengolahan Data Laporan Pajak Bulanan Berbasis Web Pada Depo Unilever Padang - Ilmawati (Riset Sinergi Indonesia (RISINDO), 2023)
Computer-based information systems have now become an important matter for meeting the needs of society. Many fields have used computer-based information systems as a means to facilitate work, both from the business world to academics and education and almost in all fields use computers as a tool to facilitate work. One of them is tax calculations at a company with an information system that can be done instantly, quickly and more efficiently. The results of the research are in the form of a web-based application as a forum for companies to manage taxpayer data, and make it easier for companies to process it